Influence of Breastfeeding Support Group (KP-ASI) on the success of exclusive breastfeeding in the Molingkapoto Community Health Center - Dwi nur octaviani; Sugianto Sugianto; Masmuni Wahda Aisya; Nurhayati Mahmud (Universitas Andalas, 2021)
Exclusive breastfeeding is giving only breast milk without giving other food and drinks to babies from birth to 6 months of age, except for drugs and vitamins. The purpose of this study was to determine the effect of breastfeeding support groups (KP-ASI) on the success of exclusive breastfeeding. The research method used is quantitative descriptive analytic which is cross sectional. The independent variable is the breastfeeding support group (KP-ASI), while the dependent variable is the success of exclusive breastfeeding. Case samples are mothers who have babies aged 6-24 months. The results of the study were based on the Chi-square statistical test, the results obtained were p = 0.001 (p <0.05), meaning that there was a significant relationship between breastfeeding support groups (KP-ASI) on the success of exclusive breastfeeding. Conclusion Breastfeeding Support Groups (KP-ASI) have a very big influence on the success of exclusive breastfeeding; most of who are assisted makes it to the exclusive breastfeeding stage.